THE RELATIONSHIP BETWEEN STRESS LEVELS AND NUTRITIONAL STATUS IN THE ELDERLY IN BAKI SUKOHARJO HEALTH CENTER - Candrika Puspitasari, Tri; Lestari Mukti Palupi, Dwi; Mei Astuti, Andriani (Proceeding of the International Conference Health, Science And Technology (ICOHETECH), 2025)
Aging is a natural biological process characterized by deterioration of physical, psychological, and social functions. These changes often cause stress in the elderly, which can negatively impact diet, appetite, and nutritional status. Poor nutritional status can trigger malnutrition, decreased immunity, degenerative diseases, and poor quality of life. This research aims to determine the relationship between stress levels and nutritional status in the elderly at the Baki Sukoharjo Community Health Center. This study uses a quantitative design with a cross-sectional approach. A sample of 64 respondents was selected using purposive sampling. Research instruments include the Perceived Stress Scale (PSS) to assess stress levels and the Mini Nutritional Assessment Short-Form (MNA-SF) to evaluate nutritional status. Data analysis used the Chi-Square test with a significance level of p < 0.05. The results showed that most respondents experienced mild stress, as many as 56 people (87.5%), while a small number experienced severe stress. The nutritional status of most respondents was at risk of malnutrition, namely 28 people (43.8%). The Chi-Square test results showed a significant relationship between stress levels and nutritional status in the elderly (p = 0.003). The results confirmed that high stress levels increase the risk of nutritional disorders, especially malnutrition. Therefore, effective stress management and education about balanced nutrition through health programs, family support, and community activities are needed to improve the quality of life of the elderly.